2016
DOI: 10.1093/mnras/stw1237
|View full text |Cite
|
Sign up to set email alerts
|

Herschel protocluster survey: a search for dusty star-forming galaxies in protoclusters atz= 2–3

Abstract: Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 80 publications
6
65
0
Order By: Relevance
“…The SMG over-density in HS1700 has a distribution that peaks near the mean optical galaxy cluster centre , but is offset ∼ 40 (320 kpc) to the north compared to the optical galaxies. Kato et al (2016) have suggested a central protocluster position ∼ 2.1 north using seven Herschel-SPIRE sources having colours consistent with z ∼ 2.3, although only one of their sources confirmed to lie within the protocluster, 1700.5, which has a spectroscopic line detections and photometric redshifts locating the source at z = 2.3 (see §3.4.3 and §3.4.5). When applying our SCUBA-2 over-density analysis at the Kato et al (2016) offset position, we find no such evidence for excess.…”
Section: Number Countsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SMG over-density in HS1700 has a distribution that peaks near the mean optical galaxy cluster centre , but is offset ∼ 40 (320 kpc) to the north compared to the optical galaxies. Kato et al (2016) have suggested a central protocluster position ∼ 2.1 north using seven Herschel-SPIRE sources having colours consistent with z ∼ 2.3, although only one of their sources confirmed to lie within the protocluster, 1700.5, which has a spectroscopic line detections and photometric redshifts locating the source at z = 2.3 (see §3.4.3 and §3.4.5). When applying our SCUBA-2 over-density analysis at the Kato et al (2016) offset position, we find no such evidence for excess.…”
Section: Number Countsmentioning
confidence: 99%
“…Kato et al (2016) have suggested a central protocluster position ∼ 2.1 north using seven Herschel-SPIRE sources having colours consistent with z ∼ 2.3, although only one of their sources confirmed to lie within the protocluster, 1700.5, which has a spectroscopic line detections and photometric redshifts locating the source at z = 2.3 (see §3.4.3 and §3.4.5). When applying our SCUBA-2 over-density analysis at the Kato et al (2016) offset position, we find no such evidence for excess. The optical centroid of the protocluster is likely the most reliable tracer of the mass distribution, as the optical sources have longer duty cycles than the more active SMGs, even though the latter are likely to be more massive on average (e.g., Chapman et al 2009).…”
Section: Number Countsmentioning
confidence: 99%
See 1 more Smart Citation
“…We derived an infrared (IR) luminosity L IR [8−1000¯m] , a dust temperature T d and a dust emissivity index β by fitting a single temperature, optically thin modified black body model to the SPIRE 250 µm (Kato et al 2016), ALMA Band 7 850 µm (Ao et al 2017;Matsuda et al in prep), ALMA Band 3 2.7 mm, and 3 mm dust continuum emission (Figure 2). The SPIRE 250 µm flux density is measured at the position of LAB18.b and applied a source confusion noise for photometry error (Kato et al 2016). The accuracy of the ALMA Band 7 850 µm absolute flux calibration is evaluated to be within 10%, which is applied for the SED fitting ( Figure 2).…”
Section: Dust Continuummentioning
confidence: 99%
“…star-forming galaxies (e.g., Venemans et al 2007;Hayashi et al 2012;Gobat et al 2013;Koyama et al 2013;Kato et al 2016;Wang et al 2016) as opposed to local galaxy clusters, which are dominated by passive elliptical galaxies. Environmental dependence of physical quantities of star-forming galaxies at z > ∼ 2, such as star-forming activity, gas metallicity, and morphology, has being investigated in many studies (see Overzier (2016) and reference therein) with the aim of understanding the early stage of the environmental effects on galaxy formation and evolution.…”
mentioning
confidence: 99%